Organic Semiconductors: Rectifying Electrical Noise with an Ionic‐Organic Ratchet (Adv. Mater. 12/2015). (March 2015) - Mikhnenko, Oleksandr V.; Collins, Samuel D.; Nguyen, Thuc‐Quyen
Abstract : An ionic‐organic ratchet transforms electronic noise into DC current. The image displays a mechanical ratchet mechanism representing the rectifying junction of the electronic device. As described by O. V. Mikhnenko, S. D. Collins, and T.‐Q. Nguyen on page 2007, This device delivers large electronic currents that are relevant for energy‐harvesting applications including radio‐frequency identification tags.